Penanaman Akar Wangi (Vetiveria zizanioides) Sebagai Upaya Mitigasi Bencana Longsor Di Desa Guntur Macan Kecamatan Gunung Sari Kabupaten Lombok Barat - Tinta Wahyu Napada S; Irma Aprianti; Zaenal Arifin; Riza Hamkary Salam (Yayasan Tajuk Indonesia, 2025)
Landslides are one of the natural disasters that cause many dangers. The landslide incident occurred on Lombok Island, precisely in Guntur Macan Village, Gunungsari District, West Lombok Regency on December 19, 2015, which claimed lives due to being buried by the landslide. This landslide disaster requires action to minimize the risk to prevent losses. The purpose of this community service activity is as an effort to reduce the impact of landslide disaster mitigation in Guntur Macan Village, Gunung Sari District. One method that can be used is by using the vegetative method. The 2023 MBKM Community Service Lecture (KKN) of the University of Mataram which was held on January 18-20, 2024 in Guntur Macan Village, Gunung Sari District, West Lombok Regency, West Nusa Tenggara raised the theme of the DESTANA (Disaster Resilient Village) activity with the concept of sloping land conservation, namely by planting fragrant roots (Vetiveria zizanioides) as an effort to mitigate landslide disasters. This activity is carried out in several stages including landslide-prone location surveys, seed preparation, socialization, land preparation, seed planting and monitoring. One of the landslide disaster management techniques is by vegetative means using fragrant root plants (Vetiveria zizanioides). The purpose of this activity is to increase the knowledge of the community regarding landslide disaster prevention, and it is hoped that there will be the development of fragrant root plants (Vetiveria zizanioides) as an effort to prevent landslide disasters.